THE EFFECT OF BRAND EQUITY ON CUSTOMER REVISIT INTENTION TO FAST-FOOD RESTAURANT IN MALAYSIA - Fairuz Abd Hakim; Suria Sulaiman; Noraslinda Mohd Said; Faizatul Khadijah Md Zin (International Journal of Accounting, Finance and Business, 2022)
The study examined the effect of brand equity on customer revisits intention toward fast-food restaurants in Malaysia. Further, the study explored the relationship between brand awareness, brand association, perceived quality, and brand loyalty on customer revisit intention using the theory of reasoned action (TRA). A survey was conducted using online questionnaires involving 388 respondents who consumed fast-food in Malaysia. Using SPSS, descriptive and correlation analyses were used to analyse the data of this study. Findings revealed that three variables positively correlate with customer revisit intention. Brand loyalty shows the strongest impact that led customer to revisit to the fast-food restaurant. The results are aligned with previous research that stated brand loyalty is the most critical determinant affecting customers’ revisit intention to the restaurants. Moreover, this research contributed to the existing body of knowledge in the field of brand management. Finally, the findings of this study can be used by restaurateurs as a reference for focusing on and managing their brand equity. In line with the study, future researchers were given implications and recommendations.